Effectiveness of Antimicrobial Filter Placement in ICU Taps to Prevent the Occurrence of HAIs by Pseudomonas aeruginosa (12-Months). (October 2020) - Chico-Sánchez, Pablo; Canovas-Javega, Sandra; Jimenez-Sepulveda, Natali J.; Leutscher-Vasen, Edith; Villanueva-Ruiz, Cesar O.; Benito-Miralles, Carmen M.; Hernandez-Maldonado, Maria; Lameiras-Azevedo, Ana S.; Sanchez-Paya, Jose
Abstract : Background: Pseudomonas aeruginosa, is the third etiologic agent of healthcare associated infections, and the most frequent pathogen in ventilator-associated pneumonia (VAP). In critical care units is associated with high mortality, long hospital stay, and high healthcare-associated costs. We evaluated the effectiveness of filter placement in the water taps in critical care units to prevent the occurrence of healthcare-associated infections (HAIa) by Pseudomonas aeruginosa . Methods: This experimental study was both cross-over and open-label in nature. We included patients admitted for >24 hours in critical care units over 24 months. The study was divided into 4 periods of 6 months each. We divided the study into 2 groups: patients in units with filters and patients in units without filters. We compared the incidence density of P. aeruginosa HAIs (number of cases divided by the number of person days) according the ECDC definition of case criteria between the groups. The 2 test was used, and the magnitude of the association was calculated as a rate ratio with a 95% confidence interval, adjusted using a Poisson regression model. Results: Overall, 1, 132 patients were included in the study: 595 in units with water tap filters and 537 in units without water tap filters. HAI incidence among patients in units with water tap filters was 5.3 per 1, 000 person days stay; without water tap filters, HAI incidence was 4.7 per 1, 000 person days stay (HR, 0.94; 95% CI, 0.47–1.90). Conclusions: The preliminary results of this study indicate a a lower incidence of P. aeruginosa HAIs in units with filters placed in water taps than in units without filters. Disclosures: None Funding: None